Competence development in fixed-term employment : paper presented at the European Conference on Educational Research (ECER), Helsinki, Finland, 25-27 August 2010 - Münchhausen, Gesa [Verfasser]; Velten, Stefanie [Verfasser] (My University, 2010)
Although in recent years several studies have been carried out on the acquisition of competencies in general and in specific professions, there is a lack of studies comparing the differences in the development of competencies between employees with a regular work, meaning traditional unlimited working contracts and employees with fixed-term contracts. Against this background the present the German Federal Institute for Vocational Education and Training (BIBB) launched a project which aims to investigate the experiences employees with fixed-term contracts have made and how they look upon their current working conditions. In addition, the project seeks to find indications for the employees' development of vocational competences. As there isn't a consensus reached yet on the definition of vocational competencies, the following working definition is used: Competencies are individual capabilities like (cognitive or practical) skills and specific knowledge which are required for carrying out tasks and solving problems. Additionally, they are influenced by motivational processes. (BIBB-Doku)
Keywords: G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; G 1.2.3 Qualifikationsentwicklungen; T 3.4 Befragung; Befristete Beschäftigung; Normalarbeitsverhältnis; Auswirkung; Kompetenzentwicklung; Arbeitszufriedenheit; Befragung